A reprodução camponesa no contexto da política de aquisição de alimentos no agreste paraibano - Souza, Jamerson Raniere Monteiro de (2024)
The present study discusses the peasant reproduction from the context of the Food Acquisition Policy (PAA and PNAE) in the agreste region from Paraíba between 2003 and 2019. It has as a territorial cut the area formed by the following cities: Alagoa Nova, Esperança, Lagoa Seca and São Sebastião de Lagoa de Roça. It also discusses peasant reproduction in Paraíba based on the theories of agrarian geography, seeking to problematize the performance of public policies for peasant agriculture with regard to food sovereignty, examining the contributions to peasant reproduction in the study area, as well as the way as the current context of democratic rupture, started in 2016, affects this reproduction. To do so, it initially presents an overview of the way in which peasant reproduction phenomenon has been debated by several intellectuals over time in the capitalist system. Showing how the interpretations give rise to contradictory perspectives, pointing out how, even in difficult situations and contrary to what many thinkers predicted, the peasantry has managed to reproduce itself, forming an important population contingent, with an intense productive and strategic role for the country. This study starts from the evaluation perspective that only late, at the end of the 20th century and the beginning of the 21st, the Brazilian State formulated public policies to support this social segment. Pointing out how these public policies resized the Brazilian peasant universe according as it was included by them on the agenda, even if they did not break with the enormous land concentration, centered on the persistence of large landowners and large monoculture, and with the neoliberal model of economy. Thus, in this study, the Food Acquisition Policies (Food Acquisition Program – PAA and National School Feeding Program – PNAE), built in the government of the Workers' Party (2003-2016), stood out. These programs started to carry out the public purchase of food from peasant agriculture to supply socially vulnerable people and school meals, eliminating the need for intermediaries. It made possible to increase the income of this population, contributing to the construction of a renewed territoriality and to the improvement of the diet of these social groups. Among other positive aspects, a national food security program was consolidated. Thus, based on a critical methodological path that included extensive bibliographic research; the collection of statistical and census data; documental research about government programs; field research that allowed the collection of primary data with the application of questionnaires, semi-structured interviews, notes, recordings, photographs, which contributed to the elaboration of this thesis.